Avaliação de um protocolo de tratamento para rejuvenescimento facial associando cosmético, eletroestimulação e mecanotransdução - Maccari, Flavia Lima Ribeiro (2019)
Facial aging is primarily characterized by the formation of wrinkles, as the skin becomes thinner and less dense, mainly due to the gradual decrease of collagen, elastin and hyaluronic acid in the dermis, causing tissue sagging. Other relevant characteristics of aging are bone resorption, redistribution of facial fat and / or loss of volume of fat pads, loss of facial muscle function in some important muscles for sustaining the face. This research was carried out to evaluate a simple, practically painless, low cost esthetic treatment that can improve the physical facial appearance of volunteers, providing a rejuvenation. The proposed treatment protocol, called biostimulation, involves three interventions, one for muscle strengthening, using the Aussie® electrical current (electrostimulation); the other with muscle relaxation, using facial massage (mechanotransduction); and finally the combination of cosmetic (Nano up factor ®) for volumization and facial lifting. For the development of this study, 56 female volunteers, aged between 40 and 50 years old, who had lines of expression in the frontal and glabellar region, periorbicular static wrinkles, deep static wrinkles in the nasogenian wrinkle and loss of muscle tone and / or volume in the malar region, were selected. The selected volunteers were randomly divided into seven groups according to the type of intervention to be applied. The patients' facial evaluation was performed in relation to the transepidermal water loss parameters, photographic evaluation and nasogenian wrinkle measurements to compare the initial and final results of each patient. Benefits from application of the techniques were observed in all volunteers, including improved skin texture and quality, improved fine-line expression, decreased depth of the nasolabial fold (dependent on the size of the groove and / or intervention used), increased facial volume in the malar region, impacting the overall rejuvenation of the face. Thus, it is possible to state that there are low-invasive techniques with lower risk of low-cost side effects or complications, which are efficient and can generate natural stimulus results for a reversal of aging. It is believed that the best treatment protocol is that we use all techniques, so we can cover a larger area of the face and optimize the results of the volunteers. Since the electric current will act at the muscle and tissue level; the manual technique, acts on the three layers of the skin, helping to reshape the face in the subcutaneous fat region, and also relaxes the frontal muscles, corrugators, procerus and depressor of the mouth angle; and the use of cosmetics is positive for hydration, firmness, nutrition and increased volume on the face.